HUBUNGAN RELIGIOUSITAS DENGAN SIKAP TAWADLU’ PADA MAHASISWA FAKULTAS USHULUDDIN IAIN WALISONGO SEMARANG ANGKATAN 2012 - Khusnul Khotimah (Living Sufism: Journal of Sufism and Psychotherapy, 2023)
This research aims to identify the relationship between religiosity and tawadlu' attitudes among students at the Ushuluddin Faculty of IAIN Walisongo Semarang class of 2012. Religiosity, as the level of depth of a person's religious beliefs and practices, is believed to have the potential to influence various aspects of behavior, including tawadlu' or humility. The research method used was quantitative with a correlational approach, involving a randomly selected sample of Ushuluddin Faculty students. Data was collected through a questionnaire that measured students' levels of religiosity and tawadlu' attitudes. Data analysis was carried out using statistical techniques to identify significant relationships between the two variables. The results of the study show that there is a significant positive relationship between religiosity and tawadlu' attitudes, with higher levels of religiosity tending to be followed by greater tawadlu' attitudes. These findings provide insight into the role of religiosity in shaping the character of tawadlu' among students, as well as its implications in developing educational programs that can strengthen the values ​​of humility in academic contexts and everyday life.